b - 9 (b, 1997)
Biography of Jyoti Basu, b. 1914, chief minister of West Bengal and a leader of the Communist Party of India (Marxist).
Includes bibliographical references (p. [1]-[8], 2nd group) and index.
In Bengali.
Keywords: Basu, Jyoti, -- 1914-2010.; Politicians -- India -- West Bengal -- Biography; Communists -- India -- West Bengal -- Biography; West Bengal (India) -- Politics and government -- 20th century; West Bengal (India) -- Biography